The segmentation of the Yugoslav communist elite, 1943-1972 - Flere, Sergej (Družboslovne razprave, 2019)
The communist elite of Yugoslavia established Yugoslavia anew during World War II. A federal communist arrangement was put in place, with the period shifting from an almost totalitarian regime towards an operationally consociational one. In this paper, we question the issue of the homogeneity and very existence of the Yugoslav ruling communist elite in the period 1943-1991. We focus on decision-making, discussions and purges by considering newly available archival sources. The article finds that while the elite was successful in taking power it was not long before the elite started to be ethnically segmented. The origins of this segmentation related to how resolution of the national question of the nations at issue was understood, in turn further driving the segmentation process. Overall, we argue that individual national elites were already established by 1972
Keywords: communism; Communist parties; čistke; elite segmentation; jugoslovanska elita; Komunistične partije; KPJ; politbiro; Politburo; Political elites; Political purges; Politične čistke; Politične elite; purges; segmentacija elite; Yugoslav elite